Janice VanCleave's physics for every kid : 101 easy experiments in motion, heat, light, machines, and sound - VanCleave, Janice Pratt; Clark, Barbara (New York : Wiley, 1991)
Presents 101 experiments relating to physics using materials readily available around the house.
Includes index.
6.5
6.5
5-8.
5-8
Keywords: Physics -- Experiments -- Juvenile literature; Experiments; Physics -- Experiments; Physics -- Experiments